2017
DOI: 10.1242/dev.149286
|View full text |Cite|
|
Sign up to set email alerts
|

RhoA regulates actin network dynamics during apical surface emergence in multiciliated epithelial cells

Abstract: Homeostatic replacement of epithelial cells from basal precursors is a multistep process involving progenitor cell specification, radial intercalation and, finally, apical surface emergence. Recent data demonstrate that actin-based pushing under the control of the formin protein Fmn1 drives apical emergence in nascent multiciliated epithelial cells (MCCs), but little else is known about this actin network or the control of Fmn1. Here, we explore the role of the small GTPase RhoA in MCC apical emergence. Disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Consistent with the force balance argument, cell-autonomous actin-based protrusion causes apical emergence (i.e. the opposite of extrusion), as is seen when multiciliated cells are added to an epithelium in Xenopus 70,71 . Thus, apical/basal contraction or expansion have distinct effects depending on whether they occur at the single-cell or population level.…”
Section: Localized Contraction and Expansion In Epithelial Morphogenesismentioning
confidence: 55%
“…Consistent with the force balance argument, cell-autonomous actin-based protrusion causes apical emergence (i.e. the opposite of extrusion), as is seen when multiciliated cells are added to an epithelium in Xenopus 70,71 . Thus, apical/basal contraction or expansion have distinct effects depending on whether they occur at the single-cell or population level.…”
Section: Localized Contraction and Expansion In Epithelial Morphogenesismentioning
confidence: 55%
“…Cytoskeletal forces are known to be integral cell autonomous features of the intercalation process. Actin-based forces, as well as small small GTPase activity, drive apical expansion of MCCs (Ioannou et al, 2013;Kim et al, 2012;Kulkarni et al, 2018;Sedzinski et al, 2016Sedzinski et al, , 2017. Additionally, we have previously shown that centriole number and the subsequent changes to microtubule (MT) accumulation can regulate the timing of apical insertion, such that cells with more centrioles or more MTs insert earlier than cells with less (Collins et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…(a) basal bodies begin to migrate, dock, and become organized (uniformly spaced) at the apical membrane (Boutin & Kodjabachian, 2019; Spassky & Meunier, 2017). (b) F‐actin and microtubules undergo dramatic reorganization just below the apical surface (Sedzinski et al, 2017; Spassky & Meunier, 2017; Werner et al, 2011). While microtubules govern cilia polarity at the local scale, that is, the polarity between neighboring cilia within a multiciliated cell, F‐actin is required for coordination of cilia polarity at the global cell, that is, between ciliated cells (Werner et al, 2011).…”
Section: Patient Driven Gene Discovery and Characterization—case Studiesmentioning
confidence: 99%